Leveraging SMEs financial inclusion through agency banking in Zimbabwe - Mashizha, Margaret; Gumbo, Lilian; Sabawo, Ashley (goodwood publishing, 2024)
Purpose: The main purpose of this study is to examine the effect of agency banking on the financial inclusion of SMEs, determine factors that influence the adoption of agency banking by SMEs, and establish an agency banking model that can be adopted to improve the financial inclusion of SMEs in Zimbabwe. Research Methodology: The study uses a mixed-method approach and is explanatory. Questionnaires and informants were used as research instruments, with a random sample of 78 respondents and 10 purposively selected agents. Inferential statistics were used to analyze the data. Results: The findings shed light on the effects of agency banking on financial inclusion and impediments to financial inclusion, and identify the channels of agency banking being used most frequently. Factors that influenced the adoption of technology were also identified. Limitations: The study was limited to one population group and one locality, although financial inclusion should ideally include all population groups. Contribution: This study recommends a unique model that can be used to enhance financial inclusion through agency banking, which has been identified as a pillar of financial inclusion. Therefore, the results are useful to policymakers and future researchers.